Speleological study of the cavern of the Ecce homo hill, in the municipality of Chimichagua, Cesar - Lascarro-Navarro, Frank David; Cormane-Tamayo, Fernando Miguel; Rojas-Martínez, Elías Ernesto (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2015)
In the municipality of Chimichagua, Cesar, there is a system of natural caves associated with carbonate sedimentary rocks, which have suffered chemical dissolution and mechanical erosion generating exokarstic and endokarstic processes, which explain the geochemical and morphological phenomena that have given rise to these cavities. This study presents the results of a speleological work performed to the cavern of the Eccehomo Hill, located in the municipality of Chimichagua department of Cesar, concluding that the lithostratigraphic units outside and inside of the cavities are micritic and micritic limestones with fossils that according to the classification of Folk (1974), belong to the Formation Aguas Blancas, of the Cogollo Group. The cavities possess throughout their extension, variety of speleothems, endokarstic process products such as stalactites, moonmilk, castings, flags, sawtooth, found in the walls and ceiling.